Enhanced Ca2+ Entry and Tyrosine Phosphorylation Mediate Nanostructure-Induced Endothelial Proliferation. (12th November 2013) - Schernthaner, Michaela; Leitinger, Gerd; Wolinski, Heimo; Kohlwein, Sepp D.; Reisinger, Bettina; Barb, Ruxandra-A.; Graier, Wolfgang F.; Heitz, Johannes; Groschner, Klaus
Abstract : Nanostructured substrates have been recognized to initiate transcriptional programs promoting cell proliferation. Specifically β -catenin has been identified as transcriptional regulator, activated by adhesion to nanostructures. We set out to identify processes responsible for nanostructure-induced endothelial β -catenin signaling. Transmission electron microscopy (TEM) of cell contacts to differently sized polyethylene terephthalate (PET) surface structures (ripples with 250 to 300 nm and walls with 1.5  µ m periodicity) revealed different patterns of cell-substrate interactions. Cell adhesion to ripples occurred exclusively on ripple peaks, while cells were attached to walls continuously. The Src kinase inhibitor PP2 was active only in cells grown on ripples, while the Abl inhibitors dasatinib and imatinib suppressed β -catenin translocation on both structures. Moreover, Gd 3+ sensitive Ca 2+ entry was observed in response to mechanical stimulation or Ca 2+ store depletion exclusively in cells grown on ripples. Both PP2 and Gd 3+ suppressed β -catenin nuclear translocation along with proliferation in cells grown on ripples but not on walls. Our results suggest that adhesion of endothelial cells to ripple structured PET induces highly specific, interface topology-dependent changes in cellular signalling, characterized by promotion of Gd 3+ -sensitive Ca 2+ entry and Src/Abl activation. We propose that these signaling events are crucially involved in nanostructure-induced promotion of cell proliferation.